Kualitas Lingkungan Fisik dan Perilaku Sehat Yang Mempengaruhi Kejadian Filariasis - Ernevi Jelita Putri; Juanda Juanda; Hardiono Hardiono (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2019)
In 2018 there were 66 cases of filariasis in Juai Subdistrict. This study aims to determine the relationship between the quality of the physical environment and health behavior with the incidence of filariasis in the District of Juai, Balangan Regency. The method of this research is analytic observation research with case control design. The study subjects consisted of 66 cases and 66 controls. Data collection is done by interview and observation. Data analysis using Chi-square test with a significance level of 0.05. The results of Bivariate Analysis show that the eight variables analyzed there are 4 variables that are proven to be related to the incidence of filariasis, namely the existence of a rubber plantation with a p-value of 0,000 (p